Effect of sintering temperature on electrical properties of SiC/ZrB2 ceramics. Issue 9 (August 2018) - Chen, Junjun; Chen, Jian; Yao, Xiumin; Chen, Zhongming; Liu, Xuejian; Huang, Zhengren
Abstract: SiC/20 wt% ZrB2 composite ceramics were fabricated via pressureless solid phase sintering in argon atmosphere at different temperature. The effect of sintering temperature on microstructure, electrical properties and mechanical properties of SiC/ZrB2 ceramics was investigated. Electrical resistivity exhibits twice significant decreases with increasing sintering temperature. The first decrease from 1900 °C to 2000 °C is attributed to the obvious decrease of continuous pore channels in as-sintered materials. The second decrease from 2100 °C to 2200 °C results from the improvement of carbon crystallization and the disappearance of amorphous layers enveloping ZrB2 grains. Additionally, the increase of sintered density with increasing temperature caused greatly advance of flexural strength, elastic modulus and Vickers hardness. But excessive temperature is detrimental to flexural strength because of SiC grain growth.